Diabetes mortality burden attributable to influenza in China: A population-based time-series analysis - Suijun Tong; Peng Yin; Jianhong Li; Zhenping Zhao; Yuchang Zhou; Maigeng Zhou (Heliyon)
Background: Previous studies have found an association between influenza, cardiovascular and cerebrovascular disease mortality, and all-cause mortality. And the vaccination of elderly diabetes is often recommended to reduce the risk of hospitalization and death. Nevertheless, no previous work has investigated the short-term impact of influenza on diabetes mortality in China. In this study, data from the national surveillance system was used to quantify the impact of influenza on diabetes-related mortality and provide guidance for the care of diabetes patients. Methods: Data from the National Influenza Surveillance Center was collected for the period between 2015 and 2019 and weekly diabetes-related deaths were calculated from China's Disease Surveillance Points System (CDSP). A distributed non-linear lag model (DLNM) was used to 1] analyze the delayed impact of high influenza virus-positive rates on diabetes-related mortality, 2] calculate the relative risk of diabetes deaths caused by high influenza virus-positive rate, and 3] estimate the attributable risk of diabetes deaths caused by influenza in China. Results: A total of 260 weeks of influenza weekly data from southern and northern China were included in this study. This resulted in 256,845 diabetes-related deaths with an average age of 73.36 years. During this period, the mean influenza virus-positive rate was 12.79 %. The relative risk of death from diabetes at high influenza positive rate was 1.33 (95 % CI [1.25, 1.40]) in southern China and 1.14 (95 % CI [1.08, 1.20]) in northern China for a 3-week lag. The estimated population attributable fraction (PAF) was 9.64 % (95 % CI [6.6 %, 12.55 %]) in southern China and 1.69 % (95 % CI [-0.04 %, 3.35 %]) in northern China. The present study suggest that reducing the influenza virus-positive rate to optimal levels could potentially prevent approximately 10,871 diabetes-related deaths annually. Conclusion: A high influenza virus-positive rate is associated with an increased risk of diabetes-related mortality. Moreover, this effect is consistent across geographical areas and gender groups. Overall, the present study suggests that the risk of diabetes-related mortality attributable to influenza is high in China.